Analisis Perlakuan Akuntansi Persediaan Berdasarkan PSAP Nomor 05 Pada Klinik Pratama Kantor Gubernur Sulawesi Utara - Walenhein Samuel Tuar; Heince Wokas (GOING CONCERN : JURNAL RISET AKUNTANSI, 2023)
Inventory is equipment or goods in a government agency to be used to support or to be handed over as a service to the public. Inventories are very important for companies, such as trading companies, manufacturers, business organizations, and also agencies in the government sector which are included in current assets. This study aims to determine whether the inventory accounting treatment at the Pratama Clinic, North Sulawesi Governor's Office is in accordance with PSAP No.5. The method used in this research is descriptive qualitative method which is a method that focuses on in-depth observation. From the results of this study it can be shown that the accounting treatment for inventory at the Pratama Clinic, North Sulawesi Governor's Office is in accordance with the Statement of Government Accounting Standards No.05, seen from the definition of inventory, classification, recognition, measurement, inventory expenses, and inventory disclosure are in accordance with PSAP No. 05 Inventory Accounting.